2021
DOI: 10.1002/asia.202100143
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐inspired Underwater Super‐Oil‐Wettability for Controlling Platelet Adhesion

Abstract: Control promotion and prevention of platelet adhesion are important for various biomedical applications. In the past, surface topography and chemical modifications have been commonly utilized for tailoring the promotion and prevention of platelet adhesion. Recently, lotus-leafinspired superhydrophobicity has appeared as an efficient avenue to prevent platelet adhesion. However, such extreme water repellent interfaces fail to perform upon prolonged and continuous exposure to aqueous phase. In this communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…10A-D). 11 Bio-mimicking this oil-repellence behavior underwater finds extensive applications in underwater oil droplet manipulation, 149 antiplatelet adhesion, 150,151 underwater sensors, 152 remediation of oil spillages, 56,[153][154][155] etc. Such interfaces are efficient in performing at extremes of temperatures, a condition where superhydrophobicity is compromised.…”
Section: Underwater Superoleophobicity: Dependence On Topography and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…10A-D). 11 Bio-mimicking this oil-repellence behavior underwater finds extensive applications in underwater oil droplet manipulation, 149 antiplatelet adhesion, 150,151 underwater sensors, 152 remediation of oil spillages, 56,[153][154][155] etc. Such interfaces are efficient in performing at extremes of temperatures, a condition where superhydrophobicity is compromised.…”
Section: Underwater Superoleophobicity: Dependence On Topography and ...mentioning
confidence: 99%
“…Furthermore, the effect of tailoring the embedded oil wettability of this reactive polymeric multilayers underwater was analyzed for platelet adhesion. 234 It was revealed that underwater superoleophilicity (after octadecylamine modification) facilitated platelet growth due to the presence of an entrapped air layer, whereas the entrapped water layer in underwater superoleophobicity (glucamine modified) inhibited the platelet growth. Thus, this unique feature of chemical reactivity was utilized to control the extreme oil wettability underwater, which further had an impact on platelet adhesion.…”
Section: Chemically Reactive Interfaces For Modulating the Liquid Wet...mentioning
confidence: 99%
“…91 Lotus-leafmimicked superhydrophobic surfaces have been recently recognized as a suitable and efficient avenue for preventing the adhesion of platelets. 92 The scope of the study of an RMLC that was used to derive two extremes of UW oil wettability 93 was extended to analyze the platelet-adhesion activity. It was observed that UW superoleophobicity inhibited platelet adhesion, and the UW superoleophilic coating promoted platelets to adhere, resulting in a highly aggregated fibrous network of adhered platelets (Figure 9I and J).…”
Section: Applications Of Rmlc-based Functional Interfacesmentioning
confidence: 99%
“…This work was further extended to investigate its potential toward the prevention of platelet attachment on a commercially available catheter tube by using the biocompatible and hemocompatible UW superoleophobic multilayer coating. 93 Thus, different, durable, and functional bioinspired wettabilities that were derived from the RMLC were observed to be highly efficient for various prospective applications.…”
Section: Applications Of Rmlc-based Functional Interfacesmentioning
confidence: 99%
“…These have the final purpose of both decreasing the fluid friction in the device to avoid clogging of tubes and apertures, and, at the same time, decreasing bacterial adhesion to limit biofouling when in contact with blood or bodily fluids [30,31]. These coatings are frequently based on disordered selfassembled micro/nanostructures that contemporarily diminish fluid friction and provide antiseptic treatment with improved liquid transport properties [32][33][34][35]. Among these activities, a special mention is deserved for the studies on the specific case of surfaces aimed at improving interaction with blood, to avoid blood cell disruption for devices to handle blood in a liquid state.…”
Section: Introductionmentioning
confidence: 99%